Translation problems of theological and philosophical concepts in the Gospel according to Philip - Kelmelytė, Gražina (Literatūra, 2019)
This article discusses the translation problems of theological and philosophical concepts in the apocryphal Gospel according to Philip. This text attributed to Valentinian Gnosticism originally was written in ancient Greek language, although now it is extant only in Coptic. The translation history of this gospel allows glancing at the transformation of theological and philosophical concepts in the texts of Early Christianity and their usage in heterodox contexts. The uniqueness of the Gospel according to Philip is revealed in its fragmentary character, lack of narrative and clear structure. All these aspects raise the question about the coherence of the theological and philosophical concepts used in the text. At first sight, it is not evident if the concept translated from Greek to Coptic reflects the identical concept or if concept gains additional connotation.
Keywords: Nag Hammadi; coptic language; early christianity; New Testament apocrypha; Valentinian Gnosticism; Gospel according to Philip